Elaboraciòn de una guía de estrategias metodológicas para mejorar la expresión corporal a través de los juegos recreativos de los niños de inicial de la Unidad Educativa Federico Gonzales Suárez de la parroquia San Miguel, cantón Salcedo en el año lectivo 2014-2015 - Espín Vaca, Manuel Vinicio (2015)
This research tries about a guide to improve body expression through recreational games in children of Federico Gonzales Suarez Initial Education Unit, from San Miguel Parish, Salcedo Canton People have the ability to learn from birth until they die, they learn from the life experience around their home, of science, their fellows, of everyday life, from their existence as a social being, listening, speaking, playing, imitating, reflecting, discussing, criticizing, discovering, and making mistakes. Oriented objectives related to the research topic were proposed….